PRAKTIK DIFERENSIASI PASCAKOLONIAL PELAKU KREATIF GRAFIS FASHION BANDUNG DI ERA EKONOMI KREATIF : BRIKOLASE HYBRID DAN TRITANGTU REGENERATIF - , Wanda Listiani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Disparities of global power relations represented in the graphic fashion works of Tiarma Sirait, Widjana and Nia Subandi are the research problems of this dissertation. Tiarma Sirait through the harajuku fashion work refers and adopts Japanese harajuku fashion. Reference to Japanese and Korean fashion mode is also done by Nia Subandi. In contrast to both women fashion designers, Widjana prefers using identities or symbols of the America such as Uncle Sam and Harley Davidson. Similarities of the three designs are repeating combination in their graphic fashion work